Makna dan Penerapan Frasa Mata Hati yang Diterangi dalam Efesus 1:18-19 - Joseph Christ Santo (Sekolah Tinggi Teologi Berita Hidup, 2018)
The Bible shows that the Ephesians who should have understood the God they worshiped were in fact still prayed by Paul so that they would have an illuminated eye of heart to know God. The focus of this research is to find out what Paul means about the enlightened eyes of the heart, why the reader of this letter needs to have the enlightened eyes of the heart, how the process of the eyes of the heart is enlightened, and what is the reason for the church today. This study used an exegesis method, by analyzing the elements of the word in the original language and in its context, so that found a principle that can be applied in today’s life. Some conclusions of this study are: Firstly, the phrase “enlightened eyes of the heart” means “it has illuminated the innermost part of man to be able to understand”. Secondly, the enlightened eyes of the heart are needed so that the reader of Ephesians grows in three ways: the hope of the call, the richness of the glory of the inheritance of the saints, and the great power of God for believers. Thirdly, to experience the enlightened eyes of the heart, one must first accept the gospel so that the Holy Spirit inhabits his heart; It is this indwelling Holy Spirit that makes the eyes of the person’s heart enlightened. Fourthly, Christians are not enough to stop accepting the gospel and their recognition of Christ, he needs to know God more deeply; for that he needs the Holy Spirit which enables him to understand his relationship with God so that he has an attitude of life in accordance with the available grace.AbstrakAlkitab menunjukkan bahwa jemaat Efesus yang seharusnya sudah mengerti tentang Allah yang mereka sembah, ternyata masih didoakan oleh Paulus agar mereka memiliki mata hati yang diterangi untuk dapat mengenal Allah. Fokus dari penelitian ini adalah untuk menjelaskan apa maksud frasa: “mata hati yang diterangi”, mengapa pembaca surat ini perlu memiliki mata hati yang diterangi, bagaimana proses mata hati yang diterangi, dan apa aplikasinya bagi gereja masa kini. Penelitian ini menggunakan metode eksegesis, yaitu dengan menganalisis unsur frasa tersebut dalam bahasa aslinya dan konteksnya. sehingga ditemukan prinsip yang dapat diaplikasikan dalam kehidupan masa kini. Kesimpulan dari penelitian ini adalah: Pertama, frasa “mata hati yang diterangi” memiliki pengertian “telah diteranginya bagian terdalam dari manusia untuk sanggup mengerti”. Kedua, mata hati yang diterangi diperlukan agar pembaca surat Efesus bertumbuh dalam tiga hal pengetahuan, yaitu pengharapan akan panggilan, kekayaan kemuliaan warisan bagi orang-orang kudus, dan kebesaran yang luar biasa dari kekuatan kuasa Allah bagi orang-orang yang percaya. Ketiga, untuk mengalami mata hati yang diterangi, seseorang terlebih dulu harus menerima Injil sehingga Roh Kudus mendiami hatinya; Roh Kudus yang mendiami inilah yang membuat mata hati orang tersebut diterangi. Keempat, orang Kristen tidak cukup berhenti pada penerimaan Injil dan pengakuannya akan Kristus, ia perlu mengenal Allah lebih dalam; untuk itu ia memerlukan Roh Kudus yang memampukannya mengerti hubungan dirinya dengan Allah sehingga memiliki sikap hidup berpadanan dengan anugerah yang tersedia tersebut.